Anti-cancer Effects of a Novel Curcumin Derivative, 4,4-Diallyl Curcumin Bis(2,2-Hydroxymethyl)Propanoate (35e), on Radio-resistant Colorectal Cancer Cells - HUANG, CHING-WEN; YANG, JAI-SING; TSAI, YUH-FENG; KUO, SHENG-CHU; JUAN, YU-NING; LIN, MENG-WEI; CHIU, YU-JEN; HSU, CHUNG-HUA (Anticancer research, 2025)
Failure of radiotherapy is a major factor leading to poor prognosis in colorectal cancer. This study investigated the anticancer effects of a novel curcumin derivative, 4,4-diallyl curcumin bis(2,2-hydroxymethyl)propanoate (35e), on radio-resistant colorectal cancer cells (HT29/RR). HT29/RR cells were established by exposing parental HT29 cells to repeated irradiation cycles. The cytotoxic effects of 35e were evaluated using MTT assays, DAPI and TUNEL staining, caspase-3 and caspase-9 activities assays, and RNA sequencing analysis. Treatment with 35e significantly reduced cell viability in a dose-dependent manner. Apoptosis induction was confirmed by chromatin condensation and DNA fragmentation (DAPI/TUNEL staining), alongside elevated caspase-3 and caspase-9 activities. RNA sequencing analysis revealed that 35e treatment altered gene expression, down-regulating pro-survival genes and up-regulating pro-apoptotic genes. Pathway analysis indicated that 35e regulated the EGFR/PI3K/AKT and NF-κB pathways, contributing to suppressed proliferation and enhanced apoptosis. 35e effectively inhibits growth and induces apoptosis in radio-resistant colorectal cancer cells by targeting multiple signaling pathways. These findings suggest that 35e is a promising therapeutic candidate for overcoming radio-resistance in colorectal cancer.